Collision‐induced mass spectrometric fragmentation of protonated dimethoate and omethoate generated by electrospray ionization. (10th January 2019) - John, Harald; Siegert, Markus; Kranawetvogl, Andreas; Thiermann, Horst
Abstract : Rationale: Dimethoate (DIM, S=P(OMe)2 ‐S‐CH2 ‐C(O)‐NH‐CH3 ) is a dimethyl phosphorodithioate pesticide widely used in agri‐ and horticulture that undergoes biotransformation in vivo by desulfuration into its more toxic oxono‐derivative omethoate (OM, O=P(OMe)2 ‐S‐CH2 ‐C(O)‐NH‐CH3 ). OM inhibits acetylcholinesterase thus provoking cholinergic crisis in vivo, ultimately leading to death. Quantitative approaches for the determination of DIM and OM in environmental and toxicological samples make use of tandem mass spectrometry (MS 2 ). Nevertheless, so far interpretation of resulting product ions is incomplete and sometimes contradictory. Methods: DIM and OM as well as their deuterated analogues (fully deuterated at both methoxy groups bound to the phosphorus atom) were analyzed by MS 2 and MS 3 after positive electrospray ionization and collision‐induced dissociation (CID) in a linear ion trap to characterize fragmentations. The accurate masses of product ions were determined in a time‐of‐flight mass analyzer. Hydrogen/deuterium (H/D)‐exchange experiments were carried out for further support of product ion identification. In addition, density functional theory (DFT) computations were used to calculate both the most stable protonation sites of DIM and OM and the changes in the diverse bond lengths after protonation. Results: Some identical and some related product ions of DIM and OM were found but also striking individual differences. Fragmentation pathways were proposed and product ions identified. Most fragmentations followed the common rules of charge migration fragmentation. DFT calculations supported experimental findings. Conclusions: Discrepancies present in the literature so far are clarified and a deeper insight is provided into the fragmentation processes of organophosphorus pesticides. The combination of diverse experimental and theoretical approaches yielded consistent results, thus demonstrating continuous progress in understanding gas‐phase reactions in MS experiments.